Efektivitas Kegiatan Story Telling Bahan Pustaka untuk Meningkatkan Pengunjung Anak Usia Dini di Perpustakaan Proklamator Bung Hatta Bukittinggi - Yulfiandri, Yulfiandri; Nelisa, Malta (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2014)
The purposes of this article are to describe: (1) the effectiveness of the implementation storytelling library materials for early childhood in the Library of Bung Hatta Bukittinggi; (2) the obstacles in the implementation of the effectiveness of storytelling activities of library materials for early childhood and how efforts to overcome these obstacles. Data were collected through observation in the Library of Bung Hatta Bukittinggi and interviews with one person librarian Library of Bung Hatta Bukittinggi and five early childhood. Analyzing data descriptively. Based on the data analysis and interviews, can be summarized as follows. First, the implementation of storytelling in the Library of Bung Hatta Bukittinggi an effective activity to increase the number of early childhood visits to the library from 25 people to 35 people and indirectly foster interest in reading to young children. Second, constraints in these storytelling activities carried out in the form of the small number of early childhood visits to the library and the lack of an invitation from parents to their children to the library makes the library's storytelling activities, as well as the efforts made by the Library of Bung Hatta Bukittinggi to overcome these obstacles be prepared all that makes this storytelling activities run with the maximum because the library has supplied children's reading room in which there are books, magazines, and other collections specifically for early childhood and made a number of visits early childhood become more increase from the previous activity executed storytelling, storytelling activities thus bringing the total number of early childhood visits to the library to be more effective.Â Keywords : effectiveness, storytelling, early childhood